Evaluation of Drought Tolerance Indices for Screening of Rice (Oryza sativa L.) Segregating Population - Kumar, Anjani; Singh, D. N. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during the monsoon season (June-September) of 2019 at the Rice Research Farm of the Department of genetics and plant breeding, Birsa Agricultural University, Kanke, Ranchi, Jharkhand, India to select drought tolerant genotypes from the 324 F2 segregants of a cross between BPT-5204 (drought susceptible) and IR-64Drt1 (drought tolerant) genotypes with the use of drought tolerant indices (DTI) under irrigated field conditions, and rainout shelter stress conditions. The experiment was laid out in augmented block design-II in nine blocks with seven check varieties in two different environments. Evaluation of correlation analysis revealed that there was a positive and significant correlation (r= 0.398) between grain yield under irrigated field condition and rainout shelter stress condition, but the correlation coefficient was low. Calculation of drought tolerance indices showed that the highest mean productivity value was observed in plant no-199 whereas the highest stress tolerance index was recorded in plant no-135. Hence, the high value of mean productivity and stress tolerance index indicated tolerant genotypes. However, the evaluation of 324 F2 segregates in respect to drought tolerance indices observed that plant no- 135, 199, 239, 222, 42, 219, 265, 195, 165 and 261 had the best genotypes with respect to best mean rank. Among the 324 F2 selected plants namely, P.N- 239 exhibited the highest grain yield under rainout shelter stress conditions, and it’s flowering was very early (98 days). This plant had confirmed two drought reproductive QTL at four markers with the help of molecular studies.